PENGARUH PENGGUNAAN METODE KESEBANGUNAN UNTUK MENINGKATKAN LITERASI SAINS SISWA KELAS VIII SMP NEGERI 2 KELAPA DUA PADA MATERI CAHAYA - Evin Kurniasih; Jayus Riyadi Solikhin (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The aim of this research is to know the increase science literacy for junior high school by using kesebangunan method on radiance subject. The type of this research is pre-experimental research with one group pretest-post test design. Sample on this research are 38 students in class VIII-B at SMP Negeri  2 Kelapa Dua. The steps of the research are observation, design research, design instrument, expert validation, revise the instrument based on validators and collect the data. Data collection is done by giving a test which is 15 questions of science literacy. The analyze technique use t test. The results showed that a significant shown PSPP is 0.00, so the hypothesis of â€œthere is an effect from using kesebangunan method for increasing science literacy in class VIII at SMP Negeri 2 Kelapa Duaâ€ is accepted. From the result we can conclude that using kesebangungan method can increase  the science literacy of class VIII at SMP Negeri 2 kelapa Dua.Keywords : Science literacy, and kesebangunan method.